Cura pastoralis w świetle Novo millennio ineunte. Kontekst Roku Eucharystii - Biela, Bogdan (Śląskie Studia Historyczno-Teologiczne, 2005)
In Novo millenio ineunte John Paul II shows us some concrete elements cura pastoralis for the Church on the beginning of third millenium. It consists of seven words – priorities: hollines, prayer, sacrament of reconciliation, priority of grace, listening to the word of God, preaching the word of God (NMI 30–40). One can say that those are some special words – keys as signs to „create Church a home and a school of communion”. Those „outer tools of communion” are rather useless, if any concret examples follow after them. That is why in searching the way for the Church in Poland, one can connect the following words – priorities: to remember with the perspective of prayer, to forgive with the sacrament of reconciliation to receive with listening to the Word of God, to be grateful with Sunday Holy Mass, to give with priority of grace, to go with preaching the word of God. The key word is faith, becouse without this fundament, there is no Church. Other words it is about transition in our ministry from ministry to evangelisation. That is why our contemporary pastoral theology, or better speaking, theology of evangelization shows „evangelization catechumenical” conception of evangelization, postulating to reread and undertake basic rules of life and christian development from catechumenal institution. Becouse of this, it is very important to understand its fundamental and basic statement of Council, that the whole Church is missionary. It is any surprise then, that in this context II Polish Plenar Council postulates to use already existing expieriences and parishal projects of renewal where a great part are church basic communities. But it is strictly connected – as John Paul postulates in Christifidelis laici – with more strict renewal of parishal structures. But before we start to programme some concrete enterprices, we – as pope says –should spread the spirituality of communion which is mainly „look lodged in Holy Trinity who lives in us and whose light should be seen in faces of people around us” (NMI 43). This look, or as – Holy Father says – contemplation of Christ visage, is able to create new energies, making us enthusiastic in concrete situations. It is also worth to say that contemplating of suffering visage of Jesus on the cross tree „seven words” were spoken. One can say that they are a specific testament giving us a programme of creating our spiritual way of life. That is why it can be very inspiriating to combine seven words of dying God – Man, with words – religious service priorities. It is important for outside tools of communion to not be soulless mechanisms or mistification of communion, but the ways of expressing and development. Celebration of Eucharisty, and mainly its top moment when Pascha of Jesus is personificated also consists those seven elements, which are somehow „shepherd’s heritage” of Jesus. This testament shows a way to christian adultery. It is also Jesus specific metodology making disciples, also strictly connected with „tools of communion” from Novo millenio ineunte, allowing us to spread the spirituality of communion.